INTERNATIOAL JOURNAL OF LIBRARIANSHI AND INFORMATION SCIENCE (IJoLIS): Abehavioural Study of Pakisani LIbrary and Information Science Community on Facevbook - Sehrish Ali , Pervaiz Ahmed, (IJoLIS, 2024)
Purpose: To explore how Pakistani LIS Community intereact with each other, especialy their behaviour on Facebook.